Expression of recombinant geobacillus SP a-amylase in pichia pastoris GS 115 - Gandhi, Sivasangkary (2014)
Amylases are a group of enzymes which are significantly applied in food and beverages, detergent, paper and textiles industries. A thermophilic microorganism producing α-amylase for sustainable high temperature operation offer many advantages such as lowering the risk of microbial contamination during substrate degradation and increasing substrate solubility. Previously, production of α-amylase SR74 in Escherichia coli expression system under regulation of T7 lac promoter in pET-32b significantly enhanced the amylase activity to 15.3 U/ml as compared to the native strain. However, current intracellular expression level in Escherichia coli was low and not that suitable for commercialization. Therefore, increased production and commercialization of thermostable α-amylase strongly warrants the need of a suitable expression system. Pichia pastoris is a currently well established methanol utilizing yeast expression system. The aim of the studies was to produce a recombinant Geobacillus sp. α-amylase SR74 in P. pastoris GS115 and characterize the biochemical properties of the purified recombinant α-amylase. In this study, the gene encoding the thermostable α-amylase SR74 in Geobacillus sp. was amplified by PCR, sequenced and sub-cloned into P. pastoris GS115 strain under the control of a methanol inducible promoter namely, alcohol oxidase I (AOX1). The recombinant plasmid was subsequently transformed into P. pastoris via electroporation method. Methanol induced recombinant expression and secretion of the protein resulted in high levels of extracellular amylase production. YPTM medium supplemented with methanol 1% (v/v) was found to be the best medium with the highest expression level (28.6 U/mL) after 120 hours of post induction. The recombinant α-amylase SR74 was purified by using affinity chromatography technique. The purified α-amylase SR74 was found to be 1.9 fold higher with a product yield of 52.6% and a specific activity of 151.8 U/mg. Purified α-amylase SR74 was found to be stable between pH 6.0-8.0 with an optimum pH of 7.0. The enzyme was found to be thermostable and thermoactive at 65°C with a half-life (t1/2) at 60°C for 88 min. Such thermostable and thermoactive characteristic of the α-amylase SR74 would be beneficial for industrial applications, especially in liquefying saccrification.